The red-listed species Thamnurgus rossicus in East Europe is a synonym of the rare Central European species, T. petzi (Curculionidae: Scolytinae) - Jordal, Bjarte H.; Gebhardt, Heiko; Mandelshtam, Michail Y. (Zootaxa, 2013)
The taxonomic status of Thamnurgus rossicus was evaluated with respect to the morphologically similar T. petzi using genetic markers. Nucleotide data from the mitochondrial COI gene revealed 2.4% variation between the European Alps and Russian steppe populations. The two nuclear DNA markers CAD and EF1á were identical across populations. In view of their similar morphology, genetic composition, and the partial overlap in host plant preferences (Ranunculaceae: Aconitum and Delphinium), T. rossicus is placed in synonymy with T. petzi.